Follow-up of sutured ulcer perforation - Puente, Sergio; Contreras, Jaime; Medina, Ricardo; Alee, Gonzalo (Cirugía del Uruguay, 1982)
One hundred and eight patients with perforated and sutured pepticulcer at Asistencia Pública in Santiago, Chile, are controlled from one to eleven years. Mortality was 13.8%, mainly in aged and poor risk patients. More than half of the Patients presented Postoperative symptoms but onlY a 25% of them required definitive surgery , specially those with previous ulcerous sYmptoms. The rest, that is 74% .of sutured patients didn't required surgery because lack of gymptoms (46.9%) or effective response to medical management (27.1 %). So, definitive surgery is necessary onlY in a scarce number of sutured patients.